Neural transplantation : an introduction - Freed, William J. (Cambridge, Mass. : MIT Press, 2000)
Although there are many scientific and philosophical reasons to study the brain, for William J. Freed, "the most compelling reason to study the brain is to be able to repair the brains of individuals with nervous system injury or disease." Advances in repairing the nervous system, as well as new data on brain development, growth, and plasticity, have revolutionized the field of brain research and given rise to the technology of brain tissue transplantation. In this book Freed discusses both what may and what may not be possible. The book covers two aspects of neural tissue transplantation research. One involves the transplantation of particular cells to repair or augment specific neuronal systems. This technique could be useful for such conditions as Parkinson's disease, Huntington's disease, chronic pain, and epilepsy. The other line of research concerns regeneration from injury, especially of the spinal cord. After providing basic background on transplantation, brain structure, and development, the book discusses Parkinson's disease, the use of transplants to influence localized brain functions, circuit reconstruction, and genetic engineering and other future technologies.
1. Introduction to transplantation in the nervous system -- 2. Brain structure and development -- 3. History of neural transplantation -- 4. Transplants and how they are used -- 5. Control groups and experiments -- 6. Regulations and guidelines for fetal tissue transplantation -- 7. Mind control and other things to worry About -- 8. Neural systems and Parkinson's disease -- 9. Neural transplantation in Parkinson's disease : a brief synopsis -- 10. Fetal brain tissue transplantation in Parkinson's disease : experiments in animals -- 11. Adrenal medulla transplantation -- 12. Studies in subhuman primates -- 13. Fetal brain tissue transplantation in parkinson's disease : clinical studies -- 14. Pain -- 15. Hypothalamus and pituitary -- 16. The cerebral cortex and stroke -- 17. Huntington's disease -- 18. Spinal cord -- 19. Visual system -- 20. Introduction to genetic engineering and neural transplantation -- 21. Growing cells in culture : stem and progenitor cells -- 22. Growing cells in culture : immortal cell lines -- 23. Genetically modified cells for producing neurotrophic factors and neurotransmitters -- 24. Direct gene transfer -- 25. Conclusions.
"A Bradford book."
Includes bibliographical references and index.
English.
Print version record.
eBooks on EBSCOhost
Keywords: Nerve tissue -- Transplantation -- Technique; Central nervous system -- Transplantation; Intracerebral transplantation; Brain Tissue Transplantation; Tissu nerveux -- Greffe -- Technique; Système nerveux central -- Greffe; Greffes intracérébrales.; Central nervous system -- Transplantation; Intracerebral transplantation